Anorectal leiomyosarcoma - Gatti, Adriana; Henderson, Eduardo; Bruno, Gerardo; Barrozzi, Carlos; Estefan, Alberto; Rondán, Mariella (Cirugía del Uruguay, 1995)
The authors present and analyse the first observa/ion of anal leiomyosarcoma in national casuistry They discuss aspects of diagnosis and treatment, both palliative and pretendingly curative. They a/so make a bibliographica/ revision of anorrectal myosarcomas as a whole, as they present similar features and evolution and literature on the first ones is ve¡y scarce.